ANALISIS TREN PENELITIAN PENDIDIKAN BIOLOGI SELAMA 1 DEKADE (2011-2020) DI UNIVERSITAS BORNEO TARAKAN - Lolyta Damanik; Fadhlan Muchlas Abrori; Aidil Adhani (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2022)
This study aimed to analyze trends in Biology Education research for a decade (2011-2020) at the University of Borneo Tarakan. This literature study research used a quantitative approach. The subject in this study was the undergraduate theses of biology education students in 2011-2020 who submitted to the UBT library. The trend was seen from the dimensions of the approach used, the research method, the field of research, and the research sample. The collected theses were based on the data collected from the library, namely 315 theses. The results showed that the quantitative approach had a significant value compared to other approaches with a percentage value of 53%, followed by a combination approach of 37% and a qualitative approach of 10%. Furthermore, based on the fields used, it was found that 84% were in the field of biology education, and 16% were in pure biology. Meanwhile, when viewed from the type/research method, the quasi-experiment and RD with samples were widely used by biology education students at the junior and senior high school levels. Keywords: research trend, approach, type/method, sample